Carbene Transfer and Carbene Insertion Reactions Catalyzed by a Mixed‐Ligand Copper(I) Complex. Issue 25 (27th June 2018) - Brenna, Stefano; Ardizzoia, G. Attilio
Abstract : The catalytic activity of the mixed‐ligand copper(I) complex [Cu(PPh3 )2 (κ 2 ‐O, O"‐lact)] (1 ) lact =l ‐(+)‐lactate has been investigated in carbene transfer and carbene insertion reactions. Complex1 catalytically promoted the diastereoselective cyclopropanation of olefins in the presence of ethyl diazoacetate (EDA), under mild conditions, and with a low catalyst loading (1 mol‐%). In the case of internal alkenes, a trans/cis ratio of up to 93:7 was reached. Moreover, compound1 easily promoted the insertion of the carbene fragment deriving from the decomposition of ethyl diazoacetate into O–H (alcohols and phenols) and N–H (amine) bonds, with formation of the corresponding ethyl 2‐alkoxyacetate, ethyl 2‐phenoxyacetate, and ethyl 2‐aminoacetate derivatives in good to high yields. Abstract : An easily prepared low‐cost copper(I) homogeneous catalyst has been investigated in carbene transfer reactions. High yields and selectivities were achieved in olefin cyclopropanation and O–H and N–H insertions.